The Levels of Depression, Anxiety and Stress on Pre and Post Knee Arthroplasty Patients - Abdul Razak, Ardilla Hanim; Zulkifly, Ahmad Hafiz; Musa, Ramli; Awang, Mohd Shukrimi; Goh , Kian Liang (IIUM Medical Journal Malaysia, 2017)
Introduction: Total knee arthroplasty represents a major advance in the treatment of degenerative joint disease. It provides excellent restoration of joint function and pain relief. The primary indication for total knee arthroplasty is to relieve pain caused by severe arthritis, with or without significant deformity. This study is to assess psychological impact pre and post arthroplasty. Materials and method: A prospective study on a cohort of patients from June 2010 untill December 2011 admitted to Hospital Tengku Ampuan Afzan for total knee replacement. Cognition tested using DASS21 (Depression Anxiety Stress Scales 21). Questionnaires were distributed 2 days before the operation and 6 months after the operation during clinic follow up. Verbal consent acquired from the patients before giving the questionnaires. Sets of questions are self-administered. Results: As for DASS 21 analysis, pre and post-operative depression was 19.91±4.92 and 6.42±3.64 respectively. Moderate depression became normal post-operative. Questions regarding positive feeling, courage to do things, hope, self- appreciation and the meaning of life were asked pre and post operatively. Pre-operative anxiety was 19.49±4.92 and post-operative anxieties at 6 months were 6.42±3.64. Severe anxiety became normal after 6 months. Patients were asked about mouth dryness, difficulty in breathing on resting, tremor, panicking and unnecessary anxiety pre and post operatively. Post-operative stress improved tremendously from 22.47±4.27 down to 8.56±3.42. Conclusion: As a conclusion, total knee arthroplasty is well accepted in Malaysia. It improves patients’ social and emotional well-being. With the current advancement in total knee arthroplasty, surgeons not only looking into the post-operative physical function, they also look after the cognitive function as the outcome measure of total knee arthroplasty.